Smart City: The main assist factor for smart cities - Triana Puspita Ningrum (School of Industrial and System Engineering, Telkom University, 2021)
Initially, A smart city was originally a solution used to deal with the environmental crisis that took place in the 20th century. Smart city concepts derive from the use of technology and knowledge to enhance society's efficiency and competitiveness. The indicators are needed that support the achievement of a smart city. We will analyze the indicators that can impact the smart city achievement in this article. The aim of this study is to identify the indicators that influence the process of developing a smart city in order to be able to help other cities to establish sustainable policies and work plans so that they can prepare themselves for a smart city consistently. From the results of content analysis and descriptions of literature reviews, it is concluded that the indicators most used in the assessment of smart cities are divided into eight groups of indicators, including governance, economy, living, mobility, environment, people, branding, and demography.